Digital atmosphere of fashion retail stores - Ha Youn Kim; Yuri Lee; Erin cho; Yeo Jin Jung (Fashion and Textiles, 2020)
Abstract This study sheds light on a prominent issue in retailing: how the digital atmosphere can affect the consumer decision-making process in a fashion retail store. Digital devices and services such as digital screens and digital signage are widely employed in fashion retail stores, transforming the way consumers make decisions about purchasing fashion products. This research investigates how the digital atmosphere affects consumers’ purchase behavior patterns based on the attention-interest-desire-search-action-share (AIDSAS) model. The findings show that attention is a key antecedent to interest, desire, and behavioral responses (search, action, and share) triggered by the digital atmosphere. The findings further suggest that attention has significantly positive effects on consumers’ purchasing patterns of utilizing the digital atmosphere in two types of fashion retail stores: sports and luxury stores. However, we find that these positive effects are more pronounced for sports retail stores than luxury retail stores. This research contributes to understanding consumer behavior related to the digital atmosphere of fashion retail stores by applying the AIDSAS model and helps uncover the stepwise relationships between attention to the store atmosphere-interest/desire and the products-behavior response. These findings have practical implications that can be applied in the fashion industry.